Making Federation Work : Federalism in Pakistan after the 18th Amendment - Faiz, Asma (Karachi : Oxford University Press, 2015)
The book presents diverse perspectives from different disciplines with coherence and an admirable focus on federalism. It adequately explains why federalism needs to be re-examined and be a subject of fresh scholarship.
includes index.
Hbk.
Keywords: Federal government -- Pakistan; Pakistan. -- Constitution (1973) -- 18th amendment; Constitution (Pakistan : 1973)